2014
DOI: 10.1530/eje-13-0797
|View full text |Cite
|
Sign up to set email alerts
|

Short-term combined treatment with liraglutide and metformin leads to significant weight loss in obese women with polycystic ovary syndrome and previous poor response to metformin

Abstract: ObjectiveThe effect of metformin on weight reduction in polycystic ovary syndrome (PCOS) is often unsatisfactory. In this study, we investigated the potential add-on effect of treatment with the glucagon-like peptide-1 receptor agonist liraglutide on weight loss in obese nondiabetic women with PCOS who had lost <5% body weight during pretreatment with metformin.MethodsA total of 40 obese women with PCOS, who had been pretreated with metformin for at least 6 months, participated in a 12-week open-label, prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
168
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(183 citation statements)
references
References 29 publications
(32 reference statements)
12
168
1
Order By: Relevance
“…Eleven patients from the present cohort had previously participated in our pilot randomized study conducted with 36 obese PCOS women demonstrating that 12-week combined treatment with liraglutide 1.2 mg QD s.c. alone or in combination with metformin was associated with significant weight loss in obese women with PCOS who had been previously poor responders regarding weight reduction with lifestyle intervention and metformin. Women lost on average 3.8 kg on liraglutide alone and 6.5 kg when liraglutide was combined to metformin [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven patients from the present cohort had previously participated in our pilot randomized study conducted with 36 obese PCOS women demonstrating that 12-week combined treatment with liraglutide 1.2 mg QD s.c. alone or in combination with metformin was associated with significant weight loss in obese women with PCOS who had been previously poor responders regarding weight reduction with lifestyle intervention and metformin. Women lost on average 3.8 kg on liraglutide alone and 6.5 kg when liraglutide was combined to metformin [11].…”
Section: Discussionmentioning
confidence: 99%
“…Some of them have previously participated in the randomized clinical trials [10,11] at the Outpatient Clinics of Department of Endocrinology, Diabetes and Metabolic Diseases at the University Medical Centre Ljubljana from November 2011 to December 2014. All the patients were assigned to liraglutide at a dose of 0.6 mg injected s.c. once per day and increased to 1.2 mg/day after 1 for 12 weeks.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Menstrual cycle frequency, the primary study endpoint, as well as ovulatory rates, hormonal parameters and metabolic markers were significantly improved in all treatment groups and to a significantly greater degree in the group taking the combined treatment, compared with the metformin-treated group (232). Another preliminary report has suggested that another GLP1 analogue, liraglutide, may have an add-on effect on weight loss in obese women with PCOS who had lost !5% body weight during a 6-month pre-treatment with metformin (233).…”
Section: Subclinical CV Disease In Pcosmentioning
confidence: 99%
“…Their outcome [11] was combined treatment with EX, and metformin for 24-week was superior to EX and metformin monotherapies in improving menstrual cyclicity, ovulation rate, androgens, insulin sensitivity measures, and reducing weight and abdominal fat. Similarly, the long-acting GLP1 analog, liraglutide, has been shown to cause significant weight loss in women with PCOS, when prescribed as monotherapy or in combination with metformin in a 12-week observational study [12]. Liu et al [13] propose that GLP-1 might be useful in alleviating β-cell stress and might improve β-cell functions and survival.…”
Section: Discussionmentioning
confidence: 99%